Desain Model Sharing Reading Literacy Berbasis e-Learning - Silvia Marni; Indriani Nisja; Rina Sartika (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
ABSTRACT This research was aimed to determine the validity of the design development of the e-Learning-Based Sharing Reading Literacy Model Design. this research was conducted using the development method. This the research is more related to formative studies with the use of exploratory studies for evaluation during the development process. In this study, it was carried out at the validation stage which involved experts in their fields. The research instrument used to obtain data is through a validity assessment by filling out a validation questionnaire sheet, consisting of 22 statement items, with 3 indicators and 7 sub indicators. The result of this research showed that development of the e-learningn-based sharing reading literacy model design is valid Keywords: Model design, reading sharing literacy, e-learning, validity